The scrambled states of America [book with audioplayer] - Keller, Laurie (Findaway World, LLC, 2020)
"At the first annual "states party," Virginia and Idaho hatch a plan to swap spots so each can see another part of the country. Before the party is over, all the states decide to switch places. In the beginning, every state is happy in its new location. But soon things start to go wrong. Florida, who switches spots with Minnesota, is freezing in the frosty northern climate, and Minnesota hasn't brought sunscreen and is getting an awful sunburn. Will the states ever unscramble themselves and return to their proper places?"--